Play as an Element of Children’s Subculture - Berezetskaya, Mariya (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The paper is concerned with sociological analysis of play as an element of the children’s subculture. Regardless of the approaches to defining the concept of the child’s subculture, its essence and significance in the child’s life, scientists agree that one of the most significant elements of the subculture is play. Play is more than just entertainment for children. In the process of playing, children learn how to interact with their peers, get to know the world around them, perceive in an accessible form the norms and rules of behavior in society. The article examines the approaches to the definition and the correlation of the concepts "children’s subculture" and "children’s culture" in foreign and domestic science, examines theoretical studies of foreign scientists on the essence of children’s culture; describes the types of play and their specificity; presents the results of the author’s research on this topic, and also draws a conclusion about the special influence of play on child’s personality formation and offers recommendations for parents in the field of children’s play behavior. Significance of the play in the structure of the children’s subculture is determined in the article, moreover, article emphasizes “non-monolithic” character of play and its ability to change. In this paper attention is drawn towards the current trend of the penetration of adult culture into the space of children’s games: game industry offers to children play with a prepared story, at the same time modern parents control the process of children’s play and organize their leisure time.